An Improved 3D Registration Method of Mobile Augmented Reality for Urban Built Environment. (10th February 2021) - Wu, Yong; Che, Weitao; Huang, Bihui
Abstract : 3D registration plays a pivotal role in augmented reality (AR) system. The existing methods are not suitable to be applied directly in the mobile AR system for the built environment, with the reasons of poor real-time performance and robustness. This paper proposes an improved 3D registration method of mobile AR for built environment, which is based on SURFREAK and KLT. This method increases the building efficiency of algorithm descriptors and maintains the robustness of the algorithms. To implement and evaluate the registration method, a smart phone-based mobile AR system for built environment is developed. The experimental result shows that the improved method is endowed with higher real-time performance and robustness, and the mobile AR 3D registration can realize a favorable performance and efficiency in the complex built environment. The mobile AR system could be used in building recognition and information augmentation for built environment and further to facilitate location-based games, urban heritage tourism, urban planning, and smart city.